Owerheidsbeleid teenoor die Afrikaners, 1806-1820 - Kotzé, C. R.(Christiaan Rudolph),1881-1950 (Stellenbosch : Stellenbosch University, 2012)
Proefskrif (Ph. D.) -- Universiteit van Stellenbosch, 1958.